On the problem of approximation of functions by algebraic polynomials with regard for the location of a point on a segment - Motornyi, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We obtain a correction of an estimate of the approximation of functions from the class W r H ω (here, ω(t) is a convex modulus of continuity such that tω '(t) does not decrease) by algebraic polynomials with regard for the location of a point on an interval.